Studying the satisfaction of patients on the outcome of an aesthetic dermatological filler treatment - De Arruda, Lúcia Helena Fávaro; Rocha, Fábio Theoto; Rocha, Armando (Wiley, 2008)
Background: Many factors contribute to extend productive life in the modern world. Competition makes people worry about physical appearance, mosftly in respect to facial and skin aging. This has motivated new developments in cosmetic dermatology and the need of evaluating patient satisfaction with the new proposed treatments. Poll questionnaire has been used for such evaluation, and the analysis of the electroencephalogram (EEG) mapping obtained while the patient answers the satisfaction questionnaire may render the results less subjective. Objectives: The purpose of this paper is to study the satisfaction of a group of 33 women (mean age, 44.years) treated with hyaluronic acid filling of nasolabial folding or lips, combining the EEG brain mapping and questionnaire techniques. Methods: At the third month of evaluation, two networked personal computers were used for the EEG recording and for presenting the patient with a questionnaire about her well-being feeling; self-evaluation of her face; her satisfaction with the results of the aesthetic treatment; how the family, friends, and people at work evaluated the result of the treatment; and her decision to repeat the treatment and to recommend it to friends and family. Results: Poll results showed that patients were feeling well and were satisfied with the results of the aesthetic treatment. Furthermore, the regression EEG mappings showed patients to be satisfied with their appearance and with the treatment involving similar brain areas. Conclusion: Patients decided to undergo the treatment because they were already considering it (54%) or because they were dissatisfied with their lips or nasolabial folding (52%). The fact that the treatment was free of charge solidified the decision. Patients consider themselves as good-looking and they wanted to preserve such a condition. © 2008 Wiley Periodicals, Inc.
Keywords: Brain mapping; Cosmetic techniques; Hyaluronic acid; Patient satisfaction; Public opinion poll; hyaluronic acid; adult; clinical article; electroencephalogram; esthetic surgery; facies; female; human; lip reconstruction; patient decision making; patient referral; patient satisfaction; priority journal; public opinion; questionnaire; self evaluation; treatment response; Adult; Algorithms; Biocompatible Materials; Brain Mapping; Cosmetic Techniques; Dermatologic Agents; Electroencephalography; Face; Female; Humans; Hyaluronic Acid; Injections, Intradermal; Middle Aged; Patient Satisfaction; Quality of Life; Questionnaires; Regression Analysis; Rejuvenation; Skin Aging; Treatment Outcome